The role of tumor necrosis factor‐α and interferon‐γ in the hyperglycemia‐induced ubiquitination and loss of platelet endothelial cell adhesion molecule‐1 in rat retinal endothelial cells. (29th May 2021) - Eshaq, Randa S.; Harris, Norman R.
Abstract: Objective: This study aimed to investigate the role of the hyperglycemia‐induced increase in tumor necrosis factor‐α (TNF‐α) and interferon‐γ (IFN‐γ) in the ubiquitination and degradation of platelet endothelial cell adhesion molecule‐1 (PECAM‐1) in the diabetic retina. Methods: Type I diabetes was induced in rats by the injection of streptozotocin, with age‐matched non‐diabetic rats as controls. Primary rat retinal microvascular endothelial cells were grown in normal or high glucose media for 6 days or in normal glucose media for 24 h with addition of TNF‐α and/or IFN‐γ. PECAM‐1, TNF‐α, IFN‐γ, and ubiquitin levels were assessed using Western blotting, immunofluorescence, and immunoprecipitation assays. Additionally, proteasome activity was assessed both in vivo and in vitro. Results: Under hyperglycemic conditions, total ubiquitination levels in the retina and RRMECs, and PECAM‐1 ubiquitination levels in RRMECs, were significantly increased. Additionally, TNF‐α and IFN‐γ levels were significantly increased under hyperglycemic conditions. PECAM‐1 levels in RRMECs treated with TNF‐α and/or IFN‐γ were significantly decreased. Moreover, there was a significant decrease in proteasome activity in the diabetic retina, hyperglycemic RRMECs, and RRMECs treated with TNF‐α or IFN‐γ. Conclusion: Tumor necrosis factor‐α and IFN‐γ may contribute to the hyperglycemia‐induced loss of PECAM‐1 in retinal endothelial cells, possibly by upregulating PECAM‐1 ubiquitination.